Operations management : (SAGE Publications, 2005)
This reader is an outstanding piece of work. It captures the essence of operations management by providing an interesting and sometimes provoking set of readings. It also provides an excellent review of the topic. Its approach to operations management is both topical and comprehensive. The editors have done an outstanding job of including many of the significant recent developments in the area, particularly in the technology and operations strategy areas' - Nigel Slack, Professor of Operations Strategy, Warwick University